Financing Management At Madrasah Tsanawiyah Private East Bekasi City - Fadllillah, Nurul; Elishabat Ishomuddin, Lisa; Latif, Apriliantoni (Studia Manageria, 2024)
Education financing is a crucial element in supporting the effectiveness and efficiency of education management. It serves as an essential financial resource in determining the success and smooth implementation of education programs, while also being an integral part of education management. This study aims to analyze and describe the management of education financing at Madrasah Tsanawiyah Swasta Annida Al Islamy, Bekasi Timur, Kota Bekasi. The research addresses the issue of low education quality, partly caused by ineffective financial management strategies. This study employs a qualitative method with a case study approach, involving the head of the madrasah, treasurer, and administrative staff as research subjects. Data collection techniques include in-depth interviews, direct observations, and document studies. Data analysis is conducted through data reduction, data presentation, and conclusion drawing, while data validity is ensured using triangulation of methods and sources. The findings reveal that budgeting, implementation, and financial evaluation processes at MTs Annida Al Islamy are well-executed and effective. The financial strategies implemented include scholarships for outstanding students, underprivileged students, orphans, and full scholarships for children of teachers. These findings affirm that effective financial management supports the sustainability of education programs and enhances accessibility for various community groups at the madrasah.